Measuring the Timing of the Bilingual Advantage - Incera, Sara (Frontiers in Psychology, 2018)
Empirical evidence has supported the idea that the bilingual advantage is a question of nuanced differences between bilinguals and monolinguals. In this article, I review findings from studies using eye tracking, mouse tracking, and event-related potentials (ERPs) which are particularly suited to measure time. Understanding the timing of the processes underlying executive function is crucial in evaluating the intricacies of the bilingual mind. Furthermore, I provide recommendations on how to best use these timing techniques to compare bilinguals and monolinguals. Temporal differences can characterize ongoing discussions of the bilingual advantage and help explain conflicting findings. Methodological and analytical innovations to better investigate the timing of the cognitive processes at play will inform a wide range of areas in cognitive science.